2001
DOI: 10.1002/1520-6807(200101)38:1<57::aid-pits6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Do elementary school-based child abuse prevention programs work? A high school follow-up

Abstract: Despite the widespread use of school-based abuse prevention programs, few studies support their effectiveness in helping children avoid victimization. Most studies that evaluate prevention programs measure changes in children's knowledge and not subsequent behavior. Further, the link between knowledge, behavior, and the ability to avoid or reduce victimization has not been established. In this study the impact of a school-based prevention program was assessed by surveying students at a high school in southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
0
30
1
3
Order By: Relevance
“…Hebert et al (2001) administered a child sexual abuse prevention program to 133 children of first to third grades and found that children involved in the prevention program showed greater preventive knowledge and skills compared to children not participating. According to Ko and Merith (2001) high school students attending the school-based abuse prevention program showed a visible increase in the level of knowledge about abuse concepts. Peterson et al (2003) reported that participants, after the child maltreatment prevention program reduced their use of spanking and violence towards children and lessened their unrealistic and dangerous beliefs about children by increasing their use of temperate discipline and skills.…”
Section: The Results Of the Effect Of The Training Program To Promotementioning
confidence: 99%
“…Hebert et al (2001) administered a child sexual abuse prevention program to 133 children of first to third grades and found that children involved in the prevention program showed greater preventive knowledge and skills compared to children not participating. According to Ko and Merith (2001) high school students attending the school-based abuse prevention program showed a visible increase in the level of knowledge about abuse concepts. Peterson et al (2003) reported that participants, after the child maltreatment prevention program reduced their use of spanking and violence towards children and lessened their unrealistic and dangerous beliefs about children by increasing their use of temperate discipline and skills.…”
Section: The Results Of the Effect Of The Training Program To Promotementioning
confidence: 99%
“…In a follow-up study, the same individuals were more likely to use the protective strategies they had been taught when confronted with threats and assaults (Finkelhor, Asdigian, & Dziuba-Leatherman, 1995b). Two further studies with high school (Ko & Cosden, 2001) and college students (Gibson & Leitenberg, 2000) showed programs were associated with reduced incidence of CSA. However, these studies harbor the limitations of retrospective recall and have not been replicated with larger and more diverse samples.…”
Section: School-based Education Programs For Prevention Of Csamentioning
confidence: 99%
“…A longitudinal survey of a nationally representative sample of youths found no relationship between exposure to school-based victimization prevention programs and victimization rates (Finkelhor, Asdigian, & Dziuba-Leatherman, 1995). Two more recent studies have found that college undergraduates (Gibson & Leitenberg, 2000) and high school students (Ko & Cosden, 2001) exposed to sexual abuse prevention programs as children experienced fewer victimization experiences than those not exposed to such programs.…”
Section: Different Factorsmentioning
confidence: 99%